Revealing the high-energy electronic excitations underlying the onset of high-temperature superconductivity in cuprates - Giannetti, Claudio (Nat Commun, 2011)
In strongly correlated systems the electronic properties at the Fermi energy (E(F)) are intertwined with those at high-energy scales. One of the pivotal challenges in the field of high-temperature superconductivity (HTSC) is to understand whether and how the high-energy scale physics associated with Mott-like excitations (|E−E(F)|>1 eV) is involved in the condensate formation. Here, we report the interplay between the many-body high-energy CuO(2) excitations at 1.5 and 2 eV, and the onset of HTSC. This is revealed by a novel optical pump-supercontinuum-probe technique that provides access to the dynamics of the dielectric function in Bi(2)Sr(2)Ca(0.92)Y(0.08)Cu(2)O(8+δ) over an extended energy range, after the photoinduced suppression of the superconducting pairing. These results unveil an unconventional mechanism at the base of HTSC both below and above the optimal hole concentration required to attain the maximum critical temperature (T(c)).